Action Beyond Exhibition: Amplifying Photovoice Through Social Action After a Community Health Needs Assessment in Philadelphia. Issue 2 (March 2022) - Dafilou, Caleb; Arisi, Maria F.; Pepe, Vincent; Hehir, Martin; McKeegan, John; Rinier, Felicia; Brawer, Rickie
Photovoice is a participatory action research method that was founded on mobilizing communities toward action. However, there is limited research detailing the action stages of photovoice that are meant to follow the initial research. In this article, we describe the action stage of a youth photovoice project conducted at the planning phase of a Community Health Needs Assessment of the Latino community in North Philadelphia. In collaboration with local leaders, we utilized photovoice to prioritize the health needs identified in the assessment. We announced a request for proposals and launched twelve, 1-year, community catalyst grants in the amount of US50, 000 each. While grants were funded and implemented, the participants continued to exhibit their findings in Philadelphia City Hall and engage with city policymakers. We developed a health policy workshop where Philadelphia youth beyond the original photovoice participants could learn advocacy skills and policy research to develop a proposal addressing a priority health need identified through photovoice. This workshop was expanded into a year-round program where participants can be matched with a career mentor, engage in professional development sessions, and continue to refine and advocate for their policy proposal. We found that successful action planning stemmed from setting goals several steps ahead of the current stage of action while enhancing the ability to center community voice in guiding action forward. Photovoice influenced decision-making throughout each of the steps taken toward action. Future research should recognize and describe action planning as a central tenet of photovoice methodologies.